Comparative efficacy and safety of the duodenal‐jejunal bypass liner in obese patients with type 2 diabetes mellitus: A case control study. Issue 8 (23rd April 2018) - Laubner, Katharina; Riedel, Nina; Fink, Katharina; Holl, Reinhard W.; Welp, Reinhard; Kempe, Hans‐Peter; Lautenbach, Anne; Schlensak, Matthias; Stengel, Rainer; Eberl, Thomas; Dederichs, Frank; Schwacha, Henning; et al.
Abstract : Aims: The duodenal‐jejunal bypass liner (DJBL) is an endoscopic device mimicking surgical duodenal‐jejunal bypass, and is indicated for the treatment of obesity‐associated type 2 diabetes mellitus. This analysis was conducted to evaluate the efficacy and safety of the DJBL in comparison to lifestyle changes and antidiabetic drugs. Materials and Methods: To determine the efficacy and long‐term safety of the DJBL, data concerning 235 obese patients with type 2 diabetes mellitus from the German DJBL registry were analysed. For comparison with standard treatment, propensity‐score‐matching with patients from the German DPV registry, including the matching parameters sex, age, diabetes duration, baseline BMI and baseline HbA1c, was applied. The final matched cohort consisted of 111 patients in the DJBL group and 222 matched control DPV patients. Results: Mean treatment time with the DJBL was 47.5 ± 12.2 weeks, mean BMI reduction was 5.0 kg/m 2 ( P < .001) and mean HbA1c reduction was 1.3% (11.9 mmol/mol) ( P < .001). Reduction of antidiabetic medications and improvements in other metabolic and cardiovascular risk parameters was observed. In comparison to the matched control group, mean reductions in HbA1c (−1.37% vs −0.51% [12.6 vs 3.2 mmol/mol]; P < .0001) and BMI (−3.02 kg/m 2 vs −0.39 kg/m 2 ; P < .0001) were significantly higher. Total cholesterol, LDL cholesterol and blood pressure were also significantly better. Conclusion: This study provides the largest, so far, hypothesis‐generating evidence for a putative positive risk/benefit ratio for treatment of obese patients with type 2 diabetes mellitus with the DJBL as an alternative treatment option for this patient population.